Job polarization: Evidence for Türkiye - Gulser, Evren; Yilmaz, Ensar (OPEN LIBRARY HUMANITIES, 2026)
In this article, we examine labour market polarization dynamics in T & uuml;rkiye. First, we use highly refined microdata to classify tasks - mainly abstract, routine and manual - to conduct analysis at the occupation-task level. Second, we find evidence for polarization driven by technological changes (the routinization hypothesis), education and increasing female employment in both low- and high-wage occupations. Lastly, we analyse the tasks performed by workers in their respective occupations and find that the occupational assignment of tasks determines their value, suggesting the existence of a structural task content.
Keywords: routinization; tasks; computerization; gender; T & uuml; rkiye; BIASED TECHNOLOGICAL-CHANGE; STRUCTURAL-CHANGE; EMPLOYMENT; TRADE; OCCUPATIONS; GROWTH; TURKEY; SKILLS; WAGES; Business & Economics